After the new social democracy: Social welfare for the 21st century - Fitzpatrick, Tony (Manchester University Press, 2003)
Social democracy has made a political comeback in recent years, especially under the influence of the Third Way. Not everyone is convinced, however, that Third Way social democracy is the best means of reviving the Left's project. This book considers this dissent and offers an alternative approach. Bringing together a range of social and political theories, After the new social democracy engages with some of the most important contemporary debates regarding the present direction and future of the Left. Drawing upon egalitarian, feminist and environmental ideas it proposes that the social-democratic tradition can be renewed but only if the dominance of conservative ideas is challenged more effectively. It explores a number of issues with this aim in mind, including justice, the state, democracy, new technologies, future generations and the advances in genetics. Lively and authoritative, After the new social democracy offers a distinctive contribution to political ideas. It will appeal to all of those interested in politics, philosophy, social policy and social studies.